Analisis Faktor Yang Mempengaruhi Struktur Modal Perusahaan Properties & Real Estate - Wibowo, Frengky; Lukman Surjadi (Jurnal Ekonomi, 2024)
The purpose of this study is to determine the effect of profitability, liquidity and company size variables on the capital structure of property & real-estate sector companies listed on the Indonesia Stock Exchange in 2019-2021. The sample of this study was determined by using purposive sampling method. The sample in this study consisted of 20 companies. The data for this study are secondary data, namely data obtained from the site www.idx.co.id. Then, the data in this study will be processed using Eviews version 12. Then, the result of this research suggests that profitability, liquidity, and company size have no significant influence on capital structure.